Distributed power flow and distributed optimization—Formulation, solution, and open source implementation. (June 2021) - Mühlpfordt, Tillmann; Dai, Xinliang; Engelmann, Alexander; Hagenmeyer, Veit
Abstract: Solving the power flow problem in a distributed fashion empowers different grid operators to compute the overall grid state without having to share grid models—this is a practical problem to which industry does not have off-the-shelf answers. We propose two physically consistent problem formulations (a feasibility and a least-squares formulation) amenable to two solution methods from distributed optimization: the Alternating direction method of multipliers (admm ), and the Augmented Lagrangian based Alternating Direction Inexact Newton method (aladin ); the latter comes with convergence guarantees. In addition, we provide open source matlab code for rapid prototyping for distributed power flow (rapidpf ): a fully matpower -compatible software that facilitates the laborious task of formulating power flow problems as distributed optimization problems. Simulation results for systems ranging from 53 buses (with 3 regions) up to 4662 buses (with 5 regions) show that the least-squares formulation solved with aladin requires just about half a dozen coordinating steps before the power flow problem is solved.